Female football players` key physical qualities: playing-position specific comparison between national-team selected and non-selected players - Savolainen, E. H. J.; Ihalainen, J. K.; Weckström, K.; Vänttinen, T.; Walker, S. (Biology of Sport, 2025)
This study investigated 1) possible differences in physical qualities between national team selected and non-selected female football players specific to playing position and 2) possible between-position differences in physical qualities specific to competition level (national team selected and non-selected players separately). One-hundred eight-six female players from Finland`s senior and youth national teams (n = 85) and Finland`s national league teams (n = 101) participated in this cross-sectional study. The following field tests were used to characterize physical qualities of the players: 30-meter sprint test with 10-meter split time for speed, countermovement jump (CMJ) for lower-body power, and 1200-meter shuttle running test (i.e. Bronco test) was used to calculate maximal aerobic speed (MAS). National team selected central- and wide-defenders and central-midfielders were faster (g = 0.74-0.94, p = 0.042-0.007) in 10-meter sprint-time and central-midfielders and forwards were faster in 30 meter sprint-time (g = 0.73-0.81, p = 0.047-0.033) compared to non-selected counterparts. Selected wide-midfielders jumped higher in CMJ (g = 0.72, p = 0.048) than non-selected counterparts. Selected central- and wide-midfielders and forwards had higher MAS (g = 0.63 1.68, p = 0.037-0.001) than non-selected counterparts. Between-position analysis revealed that selected wide-midfielders reached higher CMJ height than central-midfielders and achieved higher MAS than central-defenders. Non-selected wide-defenders were faster for 30 meter sprint time than central-defenders, central-midfielders, and forwards. Physical qualities, especially speed, differentiate national team selected players from non-selected players. Between-position differences varied between groups, but players with better physical qualities played in wide-positions in both groups.